Exploration of Geometric Elements in the Heritage Buildings of the Deli Malay Kingdom (Maimoon Palace): Geometry Analysis - Zahara , Devi; Mauliza, Elvina; Meisahruni, Reyhan Sri; Purba, Seser Novelina; Mailani, Elvi; Ketaren, Maya Alemina (Innovative: Journal Of Social Science Research, 2024)
In studying geometric concepts, a person can learn through local wisdom in the surrounding environment, for example through historical relics. The Deli Malay Traditional House is one of the historical remains of the Deli Malay Kingdom (Maimun Palace) which is an icon of the city of Medan. The aim of this research is to examine and describe geometric elements related to buildings and historical heritage in the Malay Kingdom of Deli. Researchers use qualitative analysis techniques to explain research results descriptively. This research uses descriptive qualitative research methods, including field studies, observation, documentation and literature review, to analyze geometric elements in buildings and historical heritage in the Malay Kingdom of Deli. This research shows the potential of geometric elements in the Maimun Palace as a form of learning based on local wisdom in mathematics lessons. The results of a study conducted by researchers in the Malay Kingdom of Deli showed that several parts of the house were related to geometric elements, including: 1) the roof is in the shape of a triangular pyramid, (2) the building consists of three parts, namely a circular hall, a meeting room which is triangular in shape, and a trapezoidal foyer, as well as 3) several historical relics which contain geometric elements such as jewelry boxes, musical instruments and other relics. It is hoped that the research results can be used as a contextual approach in teaching mathematics in the classroom